2018
DOI: 10.1093/hmg/ddy335
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial division inhibitor 1 reduces dynamin-related protein 1 and mitochondrial fission activity

Abstract: The purpose of our study was to better understand the effects of mitochondrial-division inhibitor 1 (Mdivi-1) on mitochondrial fission, mitochondrial biogenesis, electron transport activities, and cellular protection. In recent years, researchers have found excessive mitochondrial fragmentation and reduced fusion in a large number of diseases with mitochondrial dysfunction. Therefore, several groups have developed mitochondrial division inhibitors. Among these, Mdivi-1 was extensively studied and was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 45 publications
12
105
0
Order By: Relevance
“…* vs WT mice (*P < 0.05, **P < 0.01, ***P < 0.001). [54], several lines of evidence support this activity [41,55,56] showing that Mdivi-1 reduces Drp1 levels, prevents mitochondrial fragmentation, enhances fusion and promotes the formation of mitochondrial network and we confirm these findings. In agreement with mitochondrial improvements, Mdivi-1 ameliorated also desmin pattern in Drp/MC muscle, decreasing the accumulation of insoluble sarcoplasmic tetramers and consistently its phosphorylation in Ser-31.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…* vs WT mice (*P < 0.05, **P < 0.01, ***P < 0.001). [54], several lines of evidence support this activity [41,55,56] showing that Mdivi-1 reduces Drp1 levels, prevents mitochondrial fragmentation, enhances fusion and promotes the formation of mitochondrial network and we confirm these findings. In agreement with mitochondrial improvements, Mdivi-1 ameliorated also desmin pattern in Drp/MC muscle, decreasing the accumulation of insoluble sarcoplasmic tetramers and consistently its phosphorylation in Ser-31.…”
Section: Discussionsupporting
confidence: 86%
“…S4C) supporting a role of Drp1 only in the maintenance of normal mitochondria positioning and in the regulation of mitochondrial trafficking. Accordingly to Manczak et al [41], we found a significant Mdivi-1-dependent drop of Drp1 levels in muscle (Fig. 4b).…”
Section: Drp1 Sequesters Klc1 Allowing Transport Of Mitochondria By Ksupporting
confidence: 88%
“…The results of the present study revealed that LXA 4 significantly improved mitochondrial functions via restoration of complex‐I activity with subsequent suppression of ROS production and hence improved the mitochondrial ΔΨm collapse. The exact mechanism by which LXA 4 improved mitochondrial complex‐I activity is not well clear, but it might be due to improvement of the mitochondrial dynamics, as proved in these results. It was noticed, in these results, that Omez significantly suppress mitochondrial ROS production with subsequent elevation of mitochondrial ΔΨm and inhibition of apoptosis and oxidative stress of gastric mucosa.…”
Section: Discussionmentioning
confidence: 76%
“…To address whether maintaining mitochondrial structure could preserve sensitivity to low glucose in cells treated with multiple episodes of low glucose, we used the small molecule DRP1 inhibitor, mitochondrial division inhibitor-1 (mdivi-1). Mdivi-1 inhibits mitochondrial fission in a diverse range of mammalian cells (28). Mdivi-1 maintained mitochondrial length ( Fig 10A) and preserved low glucose induced depolarization in N38 cells treated with repeated glucose deprivation ( Fig 10B).…”
Section: Mdivi-1 Preserves the Response To Low Glucose After Repeatedmentioning
confidence: 96%